ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA SMAN 1 SINDUE TOMBUSABORA BERDASARKAN TIPE KEPRIBADIAN - Didit Dermawan; Mustamin Idris; Gandung Sugita (Jurnal Elektronik Pendidikan Matematika Tadulako, 2025)
The purpose of this study is to obtain an analytical description of students' critical thinking skills in solving trigonometry problems based on personality type. This research is a qualitative study with a descriptive approach. The results of this study are as follows: Student MHA with a guardian personality type met 1 critical thinking indicator on question number 1, which is focus, and met 6 critical thinking indicators on question number 2, namely focus, reason, inference, situation, clarity, and overview (FRISCO). Student MHA with a guardian personality type tended to be thorough in completing the given problems. Student AI with a rational personality type met 6 critical thinking indicators, namely focus, reason, inference, situation, clarity, and overview (FRISCO). Student AI with a rational personality type was good at analyzing and tended to ignore things deemed unnecessary or time-consuming. Student FA with an artisan personality type did not complete question number 1. Student FA with an artisan personality type met 3 critical thinking indicators, namely focus, reason, and inference on question number 2. Student FA with an artisan personality type tended to be slow in learning/understanding mathematical material, proven by the fact that student FA with an artisan personality type could not complete question number 1 and tended to rush in working on the problem. Student AL with an idealist personality type met 4 critical thinking indicators, namely focus, reason, inference, and situation. Student AL with an idealist personality type elaborated their answers in detail, both orally and in writing.